A radiation hybrid map of river buffalo (Bubalus bubalis) chromosome 1 (BBU1) - Miziara, M. N. [UNESP]; Goldammer, T.; Stafuzza, N. B. [UNESP]; Ianella, P. [UNESP]; Agarwala, R.; Schaeffer, A. A.; Elliott, J. S.; Riggs, P. K.; Womack, J. E.; Amaral, M. E. J. [UNESP] (Karger, 2007)
The largest chromosome in the river buffalo karyotype, BBU1, is a submetacentric chromosome with reported homology between BBU1q and bovine chromosome 1 and between BBU1p and BTA27. We present the first radiation hybrid map of this chromosome containing 69 cattle derived markers including 48 coding genes, 17 microsatellites and four ESTs distributed in two linkage groups spanning a total length of 1330.1 cR(5000). The RH map was constructed based on analysis of a recently developed river buffalo-hamster whole genome radiation hybrid (BBURH5000) panel. The retention frequency of individual markers across the panel ranged from 17.8 to 52.2%. With few exceptions, the order of markers within linkage groups is identical to the order established for corresponding cattle RH maps. The BBU1 map provides a starting point for comparison of gene order rearrangements between river buffalo chromosome 1 and its bovine homologs. Copyright (C) 2007 S. Karger AG, Basel.